CAN GDP GROWTH LINK INSTRUMENT BE USED FOR ISLAMIC MONETARY POLICY? - Uddin, Md Akther; Ali, Md Hakim; Radwan, Maha (European Journal of Islamic Finance, 2019)
In this paper, we investigate Islamic monetary policy and proposes an alternative monetary policy instrument, namely gross domestic products (GDP) growth link instrument. The modeling techniques applied are ordinary least square (OLS) and the method is applied to a dataset of 99 countries for the year 2012 and time series data for Malaysia over the period of 1983-2013. Moreover, six months (January – June 2014) daily data on Islamic and conventional interbank rates are used for the correlational study. The results tend to show that GDP growth rate adjusted for interest income and inflation can be set as a benchmark for money market instruments and reference rate for financial and capital market to set the cost of capital or rate of return. Also, we found that real interest rate is mostly not representative across 99 countries as most of the time policy rates are either determined in the money market which is usually disintegrated with the real sector of an economy, or it is fixed by the Central Bank. Islamic and conventional money market rates are found significantly correlated in the presence of dual banking system. Moreover, inflation and employment rate in the Organisation of Islamic Cooperation (OIC) countries are found higher than non-OIC countries. Therefore, the interest rate should be replaced with more representative policy rate like the GDP growth rate linked instrument which could provide a benchmark rate for pricing products in Islamic commercial banking, and an avenue for investment in the Islamic financial market.